2020
DOI: 10.3389/fimmu.2020.583008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Broadly Protective, Self-Adjuvanting Subunit Vaccine to Prevent Infections by Pseudomonas aeruginosa

Abstract: Infections caused by the opportunistic pathogen Pseudomonas aeruginosa can be difficult to treat due to innate and acquired antibiotic resistance and this is exacerbated by the emergence of multi-drug resistant strains. Unfortunately, no licensed vaccine yet exists to prevent Pseudomonas infections. Here we describe a novel subunit vaccine that targets the P. aeruginosa type III secretion system (T3SS). This vaccine is based on the novel anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…Because these are T3SS scaffold proteins required for the early stages of infection for these strains (Goure et al, 2004), vaccine escape is reduced due to the fact that mutations in these proteins would impact assembly of an active T3SS and render them nonpathogenic (Goure et al, 2004). When delivered intranasally (IN), we demonstrated that PcrV + PopB admixed with dmLT (double-mutant labile toxin from Enterotoxigenic E. coli) protected mice against acute Pa pulmonary challenge (Das et al, 2020). To reduce costs associated with their production and formulation, we genetically fused PcrV and PopB to produce PaF (Pa Fusion), which elicited protection against Pa in mouse and rat models (Das et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because these are T3SS scaffold proteins required for the early stages of infection for these strains (Goure et al, 2004), vaccine escape is reduced due to the fact that mutations in these proteins would impact assembly of an active T3SS and render them nonpathogenic (Goure et al, 2004). When delivered intranasally (IN), we demonstrated that PcrV + PopB admixed with dmLT (double-mutant labile toxin from Enterotoxigenic E. coli) protected mice against acute Pa pulmonary challenge (Das et al, 2020). To reduce costs associated with their production and formulation, we genetically fused PcrV and PopB to produce PaF (Pa Fusion), which elicited protection against Pa in mouse and rat models (Das et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When delivered intranasally (IN), we demonstrated that PcrV + PopB admixed with dmLT (double-mutant labile toxin from Enterotoxigenic E. coli) protected mice against acute Pa pulmonary challenge (Das et al, 2020). To reduce costs associated with their production and formulation, we genetically fused PcrV and PopB to produce PaF (Pa Fusion), which elicited protection against Pa in mouse and rat models (Das et al, 2020). To further reduce the potential reactogenicity associated with IN delivery of dmLT (Norton et al, 2012), we fused the A1 subunit (LTA1) to PaF (L-PaF) (Das et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in recombinant production of PopB may be due to the absence of its chaperon, PcrH. PcrH has been shown to provide structural support to PopB, leading to its optimal protein formation and production [ 20 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The translocator proteins as vaccine antigens were used also by Das et al [244]. The group used a self adjuvating construct composed of a fusion of PcrV-PopB, LT1-PcrV-PopB, or separate proteins with a separate addition of mutated heat-labile enterotoxin (dmLT).…”
Section: Type III Secretion System Effectorsmentioning
confidence: 99%